Cardiophrenic lymph node metastasis in low-grade serous ovarian adenocarcinoma - Serna-Gallegos, Tasha (Gynecol Oncol Rep, 2016)
• Cardiophrenic lymph node metastasis in low-grade ovarian carcinoma is rare. • Two cases presented here identify clinical strategies needing further attention. • Low-grade disease is treated with surgery given high chemotherapeutic resistance. • Preoperative awareness of lymph node metastasis allows for optimal debulking. • Identifying radiologic evidence of distant metastasis improves patient outcomes.